Qualitative study of user perspectives and experiences of digital inhaler technology - Ireti Adejumo; Mitesh Patel; Tricia M. McKeever; Dominick E. Shaw; Manpreet Bains (npj Primary Care Respiratory Medicine, 2022)
Abstract Electronic monitoring devices (EMDs) have been trialled in interventions to improve inhaled corticosteroid adherence and clinical outcomes. This study sought to understand the perceptions and experiences of EMD end-users. Participants recruited into a six-month EMD study were invited to a semi-structured interview. Interviews were audio-recorded, transcribed verbatim and analysed using the framework approach. Twenty-eight participants (68% female, median age 47) were interviewed. Individuals described feeling responsible for their asthma control. Recent attacks motivated a desire to maintain control. Study participation led to increased awareness of asthma status and medication use. Several individuals were open to integrating digital monitoring data with other mHealth inputs, perceiving the potential to enhance communication with clinicians and empower self-management. Openness to data sharing was tied to expectations of transparent data use. Data supported integrating beliefs and habit formation to achieve behaviour change. There was a willingness for an integrated, platform-based approach to digital self-management.